Study of Indian Market for Potential Implementation of Karakuri in Manufacturing Sector - Manickavasagam, Siddharth (2020)
India as promising destination for manufacturing industries according to Global Manufacturing Risk Index is ranked second providing opportunities to the Micro, Small and Medium Enterprises but the implementation and awareness of adopting lean as a culture is still at its nascent stage. Vast majority of the Indian manufacturing industry is transitioning to the use of IoT with high level of automation involving higher capital costs and over-automation. However, it is not a suitable solution for MSME (Micro, Small, and Medium Small Enterprises). Implementing Karakuri, a Japanese lean methodology of automating with minimum, or no electricity would aid in increasing production. This thesis focuses on introducing Karakuri in manufacturing sector and creating awareness among MSME to enable adoption of efficient manufacturing practices. With respect to Karakuri most of its application revolve around material handling solutions this thesis will try to introduce Karakuri in manufacturing industries. A thorough market research on the Karakuri market in Europe and India was performed to assess the potential along with design process of Karakuri is essential to the thesis. To proceed with the thesis, market research on Karakuri was conducted by questionnaire survey, literature research and interviews that presented the author with an overview of market in Europe and India including awareness, application, prospective growth, and present trends. To comprehend and realise the design process and a realistic case study was conducted. This thesis will present the readers with the Karakuri design process and emphasises the aspects that are important to introduce Karakuri in India.